Устройство для измерения составляющих вносимого напряжения вихретокового преобразователя - Жуков В. К. Владимир Константинович; Гольдштейн А. Е. Александр Ефремович; Овсяников П. А. Павел Аркадьевич
опубл. 15.05.87, Бюл. № 18